2020
DOI: 10.3389/fpubh.2020.00280
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Health Literacy, Social Support, Depression, and Frailty Among Community-Dwelling Older Patients With Hypertension and Diabetes in China

Abstract: Population aging is one of the major challenges facing modern society and has attracted global attention. With population aging becoming a global phenomenon, the impact of age-related diseases on health is increasing rapidly. Frailty is one of the most pressing issues facing older adults. The purpose of this study was to explore the interrelationship between health literacy, social support, depression, and frailty among older patients with hypertension and diabetes in China. No studies have investigated the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 67 publications
(100 reference statements)
13
45
0
1
Order By: Relevance
“…Using correlation analysis, the present study found that the level of medication literacy was negatively correlated with the state of frailty ( R = −0.260, p = 0.001). It is consistent with the research results by Liu et al (2020) . That is, the higher the level of medication literacy, the lower the degree of frailty.…”
Section: Discussionsupporting
confidence: 94%
“…Using correlation analysis, the present study found that the level of medication literacy was negatively correlated with the state of frailty ( R = −0.260, p = 0.001). It is consistent with the research results by Liu et al (2020) . That is, the higher the level of medication literacy, the lower the degree of frailty.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, 122 people (40%) had two or more chronic diseases and multimorbidity was an independent risk factor for CF (OR = 11.231, 96% CI = 2.912-43.322), which was in accord with the results of several studies [38][39][40]. Previous studies have shown that multiple diseases generally coexist in aging individuals and that multimorbidity is related to higher incidences of physical frailty and cognitive decline [41][42][43]. Multimorbidity may reflect age-related multiple organ and organ system failure, which reduces the body's resistance and tolerance and promotes the occurrence of physical frailty.…”
Section: Discussionsupporting
confidence: 88%
“…And seven items were answered on a 4-point Likert scale, and the others were answered in a special way (calculating numbers of support sources). Responses were calculated, and the scores of subjective support, objective support, and support utilization ranged 8–32, 1–22, and 3–12, respectively ( 35 ). Higher scores indicated a higher social support level.…”
Section: Methodsmentioning
confidence: 99%